Peramalan Jumlah Kasus Covid 19 di Jawa Timur Menggunakan Metode Triple Eksponensial Smoothing - Siti Nurul Afiyah; Nur Lailatul Aqromi; Fransiska Sisilia Mukti (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2022)
East Java is one of the areas that has many cases of covid 19, therefore the East Java provincial government must increase the number of cases of covid 19 in East Java, including by promoting the health protocol program 5. The pattern of data on cases of covid 19 in East Java shows fluctuating data patterns. Forecasting that can be used is the triple exponential smoothing method. From the test results obtained accuracy of 71.25%. It is hoped that the forecasting results can later be used as a reference for formulating East Java provincial government policies for the next period.